2018
DOI: 10.1103/physreva.98.023417
|View full text |Cite
|
Sign up to set email alerts
|

Theory of radiative electron polarization in strong laser fields

Abstract: Radiative polarization of electrons and positrons through the Sokolov-Ternov effect is important for applications in high-energy physics. Radiative spin polarization is a manifestation of quantum radiation reaction affecting the spin dynamics of electrons. We recently proposed that an analog of the Sokolov-Ternov effect could occur in the strong electromagnetic fields of ultra-high-intensity lasers, which would result in a buildup of spin polarization in femtoseconds. In this paper, we develop a density matrix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 89 publications
(145 reference statements)
1
116
0
Order By: Relevance
“…However, in a linearly-polarized (LP) laser pulse the electron spin projection onto the magnetic field axis in its rest frame oscillates with the laser field and the spin-induced net contribution is averaged to zero. Considering the SG effect being too weak as compared to the RR effect [2], present scenarios thus predict no sign of significant spin-dependent dynamics for LP laser fields with symmetric field distribution, except that asymmetry is introduced to the field itself in the few-cycle regime [12,13]. The new mechanism results from the coupling between the strong radiation reaction and spin effect, which is not active in the parameters investigated in [12] In this work, we show a new mechanism that leads to significant deflection of electrons by spin-induced effect in a symmetric LP laser field.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, in a linearly-polarized (LP) laser pulse the electron spin projection onto the magnetic field axis in its rest frame oscillates with the laser field and the spin-induced net contribution is averaged to zero. Considering the SG effect being too weak as compared to the RR effect [2], present scenarios thus predict no sign of significant spin-dependent dynamics for LP laser fields with symmetric field distribution, except that asymmetry is introduced to the field itself in the few-cycle regime [12,13]. The new mechanism results from the coupling between the strong radiation reaction and spin effect, which is not active in the parameters investigated in [12] In this work, we show a new mechanism that leads to significant deflection of electrons by spin-induced effect in a symmetric LP laser field.…”
Section: Introductionmentioning
confidence: 78%
“…· the photon energy fraction. The theory for arbitrarily polarized electrons is further developed by D Seipt et al in [12]. For electron polarization vector of s in its rest frame, the radiation probability rate is [12] d d y…”
Section: Qed Spin-dependent Radiation-reaction Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has shown that photon polarisation [51] and electron spin [52][53][54] could affect the development of the cascade. These effects are not considered here.…”
Section: Discussionmentioning
confidence: 99%